Persepsi Konsumen dan Strategi Pemasaran dalam Pengembangan Agroindustri Tiwul Instan Produksi KWT Kenanga Ponorogo - Agnes Ayu Rahmawati; Joni Murti Mulyo Aji (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
KWT Kenanga is an agro-industry driver made from cassava in Sidoharjo Village by processing cassava into instant tiwul. However, the number of production and sales of instant tiwul product "KWT Kenanga" tends to fluctuate and the remaining product is relatively large every month. Promotion of their products is not intensively carried out so that the market share of instant tiwul is relatively narrow. The purpose of this study was to determine consumer perceptions to formulate a marketing strategy with the application of STP and marketing mix. The analytical methods used are IPA analysis, CSI analysis, crosstabs analysis, cluster analysis, and biplot analysis with a sample of 85 people. The results showed that: 1) Based on the IPA analysis, the attributes whose performance had met consumer expectations were the attributes of taste, price, and benefits, then the attributes that needed to be improved were the attributes of packaging design, texture, and color. Based on the CSI analysis, the overall consumer perception is classified as "satisfied" with a CSI value of 78.4%, 2) Based on the cluster analysis, the groups formed are 3 segments. Based on crosstabs analysis, significant variables include age, occupation, frequency of purchase, interest in re-consuming, so that the selected target market is cluster 1 and cluster 3. Based on the biplot analysis, the positioning that can be arranged is "Instant tiwul is an alternative food to replace rice that is sold at affordable prices but has several health benefits".